Peripapillary Vascular Reactivity in Primary Open-Angle Glaucoma With High Myopia by Using Optical Coherence Tomography Angiography - Fan, Xintong; Xu, Huan; Zhai, Ruyi; Sheng, Qilian; Sun, Yanan; Shao, Tingting; Kong, Xiangmei (Frontiers in Medicine, 2022)
Purpose: To evaluate peripapillary vascular reactivity in primary open-angle glaucoma (POAG) with and without high myopia (HM) by using optical coherence tomography angiography (OCTA). Methods: This prospective study enrolled 48 eyes with POAG, including 16 and 32 eyes with and without HM, respectively. The retinal peripapillary vessel density (VD) was repeatedly assessed using OCTA at baseline and after a hyperoxia test (breathing 80% oxygen). The VD changes between different oxygenation conditions were calculated to reflect the vasoreactivity. Linear regression was performed to determine the relationship between myopia and retinal vascular reactivity in patients with POAG. Systemic hemodynamic characteristics were also evaluated under both conditions. Results: The VD was significantly reduced after hyperoxia in the whole image (baseline and hyperoxia: 41.4±4.5 and 38.8±4.4, respectively, P<.001) and in the peripapillary regions (44.3±5.7 and 41.1±5.4, respectively, P<.001) in POAG eyes without HM. However, in eyes with HM, the whole-image VD in hyperoxia was not significantly different from the baseline (baseline and hyperoxia: 40.5±6.2 and 40.2±6.2, respectively, P=.481). The VD changes in eyes with HM were significantly smaller than those in eyes without HM in both the whole image (0.3±1.8 and 2.6±2.0, respectively, P<.001) and peripapillary regions (1.1±2.0 and 3.2±2.3, respectively, P=.003). Linear regression results showed a significant correlation between retinal vascular reactivity and spherical equivalent (SE) (=0.28, P<.001, R2=0.31) and axial length (AL) (=-0.72, P<.001, R2=0.33). Conclusions: Retinal vasoreactivity of peripapillary capillaries in POAG eyes with HM was significantly impaired in comparison with that in POAG eyes without HM. A lower peripapillary vascular response was significantly associated with worse SE and elongated AL.